Entrepreneurial Market Orientation Relationship to Performance - Cameroon SME Perspective - Belinda, Nchang (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The aim of this research is to explore Cameroon Small Medium Enterprise (SMEs) internationalization performance (IP) at the standpoint of tactical market orientation (MO) moderating on entrepreneurial interacting or networking (NT). It make evident the linking meaning of tactical market alignments and NT contained by the background of „what‟ and „how‟ are the foundations of theoretical structure that are suitably to designate the principal concepts. This exploration embraces a quantifiable method using multi-linear regression from 51 appraised Cameroonian SME‟s resulting from authorized citation of Cameroon SMEs book commercial reference book 6th edition. The theoretical structure was resituated and constructed on the point of view that MO donated considerably to SMEs intercontinental enactments with the existence of NT. The discoveries exposed varied outcomes with the crossing point of market MO and NT (MONT) established meaningfully affirmative connection while MO unaccompanied revealed positive but low correlation in spite of exhibiting substantial on IP. The results entail the conglomerates effects of great market-network/ moderate-entrepreneurship alignment structures are supreme necessary internationalize fundamental circumstance for an unindustrialized market setting such as in the Cameroon setting. This investigation has merely been piloted based on cross-sectional revision. Consequently, forthcoming investigation should transmit towards this track of exploration by following longitudinal qualitative findings in order to improve further understandings. Keywords: Small medium enterprises, Market orientation, Networking, International Performance, Cameroon.

ÖZ: Bu çalışmanın amacı Kamerun‟daki Küçük ve Orta Boy İşletmelerin (KOBİ) taktiksel pazar odaklılık ile girişimcilik veya ağ oluşturma boyutlarının uluslararası faaliyet performanslarına etkisini incelemektir. Taktiksel pazar uygulamalarının ve ağ oluşturma boyutlarının teorik yapıya uygun olduğu da bu çalışma ile desteklenmiştir. Araştırmadaki bulgular çoklu regresyon ile incelenmiş ve kavramsal modeldeki faktörler analiz edilmiştir. Araştırmamızın örneğini oluşturan 51 KOBİ, Kamerun KOBİ listesinden seçilmiştir. Pazar odaklılık kavramı ile uluslararası ağ oluşumuna dayanarak teorik yapı oluşturulmuştur. Ağ oluşturulması kavramsal modelimizde moderator olarak ele alınmış ve KOBİ‟lerin kıtalar arası faaliyetlerinde etkin olacağı ortaya konmuştur. Araştırma sonucunda elde edilen bulgular pazar odaklı olma ile ağ oluşturmanın KOBİ‟lerin uluslararasılaşmasına olumlu etkisi olduğu sonucuna varılmıştır. Anahtar Kelimeler: Küçük ve Orta Boy İşletmeler, Pazar odaklılık, Ağ oluşturma, Uluslararası Performans, Kamerun
Master of Business Administration in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Small and Medium business-Cameroon; Small medium enterprises; Market orientation; Networking; International Performance; Cameroon